2008
DOI: 10.1111/j.1365-2699.2007.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘oriental’ component of the Balkan flora: evidence of presence on the Thracian Plain during the Weichselian late‐glacial

Abstract: Aim To obtain palaeobotanical evidence enabling evaluation of the viability of the hypothesis that the 'oriental' element of the Balkan flora reached south-east Europe from Turkey prior to the Holocene, probably via the Thracian Plain during a late Quaternary glacial stage but no later than the late Weichselian.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…In recent years abundant paleoecological information since the termination of the last glaciation has been collected from terrestrial sites with relatively consistent chronological control in the Rila Tonkov, 2000, 2011;Tonkov et al, 2008Tonkov et al, , 2011Tonkov et al, , 2013a and northern Pirin mountains (Tonkov et al, 2002;Stefanova and Ammann, 2003;Stefanova et al, 2006a,b;Marinova and Tonkov, 2012), and the Thracian lowlands (Magyari et al, 2008;Connor et al, 2013). These studies revealed the basic stages and trends in vegetation development, climate fluctuations, possible location of refugia, tree migrations, and patterns of human impact and they have also enriched our knowledge about the important role of the Balkans as one of the key areas for the postglacial plant recolonization of Europe (Lang, 1994;Willis, 1994;Bozilova et al, 1996;Tzedakis, 2004;Jalut et al, 2005;Magri et al, 2006;Tzedakis, 2009;Fletcher et al, 2010;Tzedakis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years abundant paleoecological information since the termination of the last glaciation has been collected from terrestrial sites with relatively consistent chronological control in the Rila Tonkov, 2000, 2011;Tonkov et al, 2008Tonkov et al, , 2011Tonkov et al, , 2013a and northern Pirin mountains (Tonkov et al, 2002;Stefanova and Ammann, 2003;Stefanova et al, 2006a,b;Marinova and Tonkov, 2012), and the Thracian lowlands (Magyari et al, 2008;Connor et al, 2013). These studies revealed the basic stages and trends in vegetation development, climate fluctuations, possible location of refugia, tree migrations, and patterns of human impact and they have also enriched our knowledge about the important role of the Balkans as one of the key areas for the postglacial plant recolonization of Europe (Lang, 1994;Willis, 1994;Bozilova et al, 1996;Tzedakis, 2004;Jalut et al, 2005;Magri et al, 2006;Tzedakis, 2009;Fletcher et al, 2010;Tzedakis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their geographical position on the junction of migration routes from central Europe, the Mediterranean Basin or even eastwards from Pontic and Asia Minor resulted in a melting pot of taxa from different biogeographic areas (Magyari et al 2008). Actually, the south of the Balkan Peninsula and Crete constitute two of the ten hot-spots considered in the Mediterranean Basin (Médail and Quézel 1997).…”
Section: Introductionmentioning
confidence: 99%
“…New paleobotanical studies indicate that some high-altitude Irano-Anatolian elements (e.g., Celtis tournefortii, Juniperus cf. excelsa) may have expanded into SE Europe during the last glacial period (Magyari et al, 2008).…”
Section: Phytogeographic Boundary Shifts In Response To Climate Changementioning
confidence: 99%